A Novel Multidisciplinary Approach for the Thermo‐Rheological Study of Volcanic Areas: The Case Study of Long Valley Caldera. Issue 2 (10th February 2021) - Gola, G.; Barone, A.; Castaldo, R.; Chiodini, G.; D'Auria, L.; García‐Hernández, R.; Pepe, S.; Solaro, G.; Tizzani, P.
Abstract: We propose a novel multidisciplinary approach to image the thermo‐rheological stratification beneath active volcanic areas, such as Long Valley Caldera (LVC). We performed a thermal fluid dynamic model via optimization procedure of the thermal conditions of the crust. We characterize the topology of the hot magmatic bodies and the hot fluid circulation (the permeable fault‐zones), using both a novel imaging of the a and b parameters of the Gutenberg‐Richter law and an innovative procedure analysis of P‐wave tomographic models. The optimization procedure provides the permeability of a reservoir (5.0 × 10 −14  m 2 ) and of the fault‐zone (5.0  ·  10 −14 – 1.0  ×  10 −13  m 2 ), as well as the temperature of the magma body (750–800°C). The imaging of the rheological properties of the crust indicates that the brittle/ductile transition occurs about 5 km b.s.l. depth, beneath the resurgent dome. There are again deeper brittle conditions about 15 km b.s.l., agreeing with the previous observations. The comparison between the conductive and the conductive‐convective heat transfer models highlights that the deeper fluid circulation efficiently cools the volumes above the magmatic body, transferring the heat to the shallow geothermal system. This process has a significant impact on the rheological properties of the upper crust as the migration of the B/D transition. Our findings show an active magmatic system (6–10 km deep) and confirm that LVC is a long‐life silicic caldera system. Key Points: A novel multidisciplinary data fusion approach to image the thermo‐rheological stratification beneath active volcanic areas A novel imaging of the seismic a and b parameters and an innovative procedure analysis of P‐wave tomographic models We highlighted the impact of fluid circulation on the rheological stratification of the crust beneath Long Valley Caldera